The Role of T Helper 22 Cells in Dermatological Disorders - Pan, Yu; Du, Dan; Wang, Lian; Wang, Xiaoyun; He, Gu; Jiang, Xian (Frontiers in Immunology, 2022)
T helper 22 (Th22) cells are a newly identified subset of CD4+ T cells that secrete the effector cytokine interleukin 22 (IL-22) upon specific antigen stimulation, barely with IFN-γ or IL-17. Increasing studies have demonstrated that Th22 cells and IL-22 play essential roles in skin barrier defense and skin disease pathogenesis since the IL-22 receptor is widely expressed in the skin, especially in keratinocytes. Herein, we reviewed the characterization, differentiation, and biological activities of Th22 cells and elucidated their roles in skin health and disease. We mainly focused on the intricate crosstalk between Th22 cells and keratinocytes and provided potential therapeutic strategies targeting the Th22/IL-22 signaling pathway.